Effectiveness of dexamethasone in preventing postoperative nausea, vomiting, pain, and enhancing recovery after adult tonsillectomy: a randomized controlled trial - Tran , Thi Thuy; Phan , Tran Phuc Bao; Phan , Thang; Pham , Thi Minh Thu; Nguyen , Van Minh (Tạp chí Y Dược Huế, 2025)
Background: Tonsillectomy in adults is associated with postoperative nausea, vomiting (PONV), pain, and delayed recovery. Dexamethasone may alleviate these complications. Objective: To evaluate the effectiveness of a single 8 mg intravenous dose of dexamethasone administered at induction in reducing PONV, postoperative pain, and improving recovery after adult tonsillectomy. Methods: This prospective, randomized controlled trial included 109 patients (ASA I - II, aged 16 - 60 years) undergoing elective tonsillectomy under general anesthesia. Participants were randomized to receive dexamethasone 8 mg IV (Group D, n = 55) or 0.9% NaCl (placebo, n = 54) at induction. Outcomes included PONV incidence and severity, pain scores (visual analog scale, VAS) at rest and during swallowing, time to first oral intake, and Quality of Recovery-15 (QoR-15) scores at 24 hours. Results: PONV incidence was lower in Group D (9.1%) than in placebo (29.6%) (p < 0.05). Median VAS scores at rest and during swallowing were significantly lower in Group D at all time points (p < 0.05). Time to first oral water intake (4.9 ± 1.7 h vs. 8.0 ± 3.3 h) and food intake (15.6 ± 0.6 h vs. 19.4 ± 0.6 h) was shorter in Group D (p < 0.001). Mean QoR-15 scores were higher in Group D (128.3 ± 7.6) than in placebo (117.5 ± 9.6, p < 0.001). Conclusion: A single 8 mg IV dose of dexamethasone at induction significantly reduces PONV and pain, accelerates oral intake, and improves QoR-15 scores after adult tonsillectomy.